2022
DOI: 10.3390/nano12060939
|View full text |Cite
|
Sign up to set email alerts
|

VO2 as a Highly Efficient Electrocatalyst for the Oxygen Evolution Reaction

Abstract: Herein, we report high electrocatalytic activity of monoclinic VO2 (M1 phase) for the oxygen evolution reaction (OER) for the first time. The single-phase VO2 (M1) nanoparticles are prepared in the form of uniformly covering the surface of individual carbon fibers constituting a carbon fiber paper (CFP). The VO2 nanoparticles reveal the metal-insulator phase transition at ca. 65 °C (heating) and 62 °C (cooling) with low thermal hysteresis, indicating a high concentration of structural defect which is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…State-of-the-art OER catalysts are based on precious metals such as IrO 2 and RuO 2 with the η values from 200 mV (in acid) to 300 mV (in base), but the scarcity and high costs of those materials restrict their large-scale applications [ 7 ]. In this regard, the earth-abundant transition metal oxides based on Co, Ni, Fe, and V have been extensively investigated as alternative OER catalysts [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art OER catalysts are based on precious metals such as IrO 2 and RuO 2 with the η values from 200 mV (in acid) to 300 mV (in base), but the scarcity and high costs of those materials restrict their large-scale applications [ 7 ]. In this regard, the earth-abundant transition metal oxides based on Co, Ni, Fe, and V have been extensively investigated as alternative OER catalysts [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ECSA was determined from eqn (2), and the double-layer capacitance current is directly proportional to the electrochemical active surface area (ECSA). 31 The linearity obtained from the plot of geometrical current density and scan rate revealed a diffusion-controlled electrocatalytic process. The facile electron flow in the process is due to diffusion.where Δ j is current density (mA cm −2 ), and V is potential.…”
Section: Resultsmentioning
confidence: 93%
“…The electrochemical active surface area (ESCA) is a good descriptor of the electrochemical activity toward hydrogen evolution reaction. The ECSA was determined from equation 2, double-layer capacitance current is directly proportional to the electrochemical active surface area (ECSA) 31 . The linearity obtained from the plot of geometrical current density and scan rate revealed a diffusion-controlled electrocatalytic process.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…From Figure a, it is observed that the hybrid electrocatalysts showed a C dl value of 60.06, 154.2, and 60.92 mF cm –2 respectively. The electrochemical activity is well interpreted through the electrochemical active surface area (ESCA), which is directly proportional to the double-layer capacitance . The linear plot (Figure a) revealed that the electrocatalytic process is a diffusion-controlled process.…”
Section: Resultsmentioning
confidence: 94%
“…The electrochemical activity is well interpreted through the electrochemical active surface area (ESCA), which is directly proportional to the double-layer capacitance. 24 The linear plot (Figure 8a) revealed that the electrocatalytic process is a diffusioncontrolled process. The current is due to the facile electron flow at the electrode/electrolyte interface.…”
Section: Vibrating Sample Magnetometer (Vsm) M(ii)-mentioning
confidence: 99%